2023
DOI: 10.3390/molecules28176287
|View full text |Cite
|
Sign up to set email alerts
|

Decaborane: From Alfred Stock and Rocket Fuel Projects to Nowadays

Igor B. Sivaev

Abstract: The review covers more than a century of decaborane chemistry from the first synthesis by Alfred Stock to the present day. The main attention is paid to the reactions of the substitution of hydrogen atoms by various atoms and groups with the formation of exo-polyhedral boron–halogen, boron–oxygen, boron–sulfur, boron–nitrogen, boron–phosphorus, and boron–carbon bonds. Particular attention is paid to the chemistry of conjucto-borane anti-[B18H22], whose structure is formed by two decaborane moieties with a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 353 publications
0
2
0
Order By: Relevance
“…The most readily available decaborane (14) B 10 H 14 , orthoand meta-carboranes 1,2-C 2 B 10 H 12 and 1,2-C 2 B 10 H 12 , decahydro-closo-decaborate [B 10 H 10 ] 2− and octadecahydro-conjucto-eicosaborate [trans-B 20 H 18 ] 2− anions (Figure 1) are considered as the boron clusters. Decaborane (14) can be readily prepared in a two-step procedure from sodium tetrahydroborate NaBH 4 [47]. The well-known ortho-carborane is obtained by introducing the acetylene molecule into the open boron cage of decaborane (14), and its thermal isomerization leads to meta-carborane [48].…”
Section: Introductionmentioning
confidence: 99%
“…The most readily available decaborane (14) B 10 H 14 , orthoand meta-carboranes 1,2-C 2 B 10 H 12 and 1,2-C 2 B 10 H 12 , decahydro-closo-decaborate [B 10 H 10 ] 2− and octadecahydro-conjucto-eicosaborate [trans-B 20 H 18 ] 2− anions (Figure 1) are considered as the boron clusters. Decaborane (14) can be readily prepared in a two-step procedure from sodium tetrahydroborate NaBH 4 [47]. The well-known ortho-carborane is obtained by introducing the acetylene molecule into the open boron cage of decaborane (14), and its thermal isomerization leads to meta-carborane [48].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance their physical and mechanical properties, these alloys are modified with a small amount of boron [8][9][10], which is a structure-modifying impurity in the intermetallic compound. For example, materials based on Ti-43Al-6Nb-1Mo-1Cr-(0, 0.6)B were manufactured [11], and it was observed that the addition of boron, along with a multi-stage forging process, improves the microstructure and significantly increases the ultimate tensile strength of alloys.…”
Section: Introductionmentioning
confidence: 99%